Kerajaan Allah sebagai Konsep Sentral Teologi Perjanjian Lama: Kajian Biblikal atas Relasi Perjanjian, Keadilan, dan Kesetiaan - Tanugraha, Yoas; Nesimnasi, Ruben (Jayapangus Press, 2025)
The Kingdom of God is a central concept that unifies the theological structure of the Old Testament (OT), spanning from God's cosmic sovereignty to the eschatological direction of salvation history. This study aims to analyze the Kingdom of God as an integral theological paradigm by tracing the ontological foundations of God's reign, the relational mode through covenant (Ex 19:5-6; 2 Sam 7:12-16), and the ethical foundations of justice and faithfulness (Ps 97:2; Isa 11:3-5). Using a qualitative-theological method with historical-grammatical exegesis and canonical hermeneutics, this study examines key OT texts to map out a consistent and interrelated structure of the kingdom. The results show that the Kingdom of God functions as the axis of Old Testament theology: cosmic sovereignty establishes the basis of divine government, the covenant provides a relational framework for the life of the people, and justice and faithfulness become the norms of the kingdom that shape the historical praxis of Israel. The eschatological dimension reveals the direction of the kingdom toward universality and eternity (Isa 2:2-4; Dan 7:14; Zech 14:9). This study also affirms a natural continuity with the New Testament, where Jesus' proclamation that “the Kingdom of God is at hand” (Mark 1:15) appears as the fulfillment of the kingdom structure that had been built in the Old Testament. The main contribution of this study lies in the formulation of the kingdom paradigm as a hermeneutical framework that helps to read the theological unity of the Old and New Testaments, as well as enriching the study of Old Testament theology through the integration of ontological, covenantal, ethical, and eschatological dimensions. These findings open up space for further research on the ethical, ecclesiological, and missionary implications of the Kingdom of God in the life of the people.